THE INFLUENCE OF PROJECT BASED LEARNING MODELS ON SCIENCE TECHNOLOGY, ENGINEERING AND MATHEMATICS APPROACH TO COLLABORATIVE SKILLS AND LEARNING RESULTS OF STUDENT - Zulvi Ridhotul Rizkiyah; Slamet Hariyadi; Ika Lia Novenda (ScienceEdu: Jurnal Pendidikan IPA, 2020)
The main problem in learning science which until now has not yet been completely solved is by the assumption in students that this lesson is difficult to understand and understand. The main factor of this reality seems to be due to the lack of connection in learning science with everyday life. The Project-Based Learning model with the STEM approach (Science, Technology, Engineering, and Mathematics) is very suitable to overcome these problems because the learning process involves students working collaboratively by combining two or more disciplines. This research is a quasi-experimental which aims to determine the effect of the Project-Based Learning learning model with the STEM approach to collaborative skills and student learning outcomes. Assessment of students' collaborative skills is obtained when students work on assignments in groups with the guidelines for the collaborative skills rubric. Student learning outcomes are obtained from pre-test and post-test scores.